2013
DOI: 10.1111/cen.12175
|View full text |Cite
|
Sign up to set email alerts
|

Favourable metabolic effects of a eucaloric lower‐carbohydrate diet in women with PCOS

Abstract: Summary Objective Diet-induced reduction in circulating insulin may be an attractive nonpharmacological treatment for women with polycystic ovary syndrome (PCOS) among whom elevated insulin may exacerbate symptoms by stimulating testosterone synthesis. This study was designed to determine whether a modest reduction in dietary carbohydrate (CHO) content affects β-cell responsiveness, serum testosterone concentration and insulin sensitivity in women with PCOS. Design In a crossover design, two diets (‘Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 41 publications
5
86
0
3
Order By: Relevance
“…85 One trial included a diet with <30% carbohydrates, six trials included diets with 40% carbohydrates and four studies with 41-45% carbohydrates. 41,42,76,83,[86][87][88][89][90][91][92] Douglas et al 92 compared the effects of three eucaloric diets: 1) standard (16% protein, 56% carbohydrate, 31% fat), 2) moderately low-carbohydrate (15% protein, 43% carbohydrate, 45% fat) and 3) high monounsaturated fatty acid (MUFA) diets (15% protein, 55% carbohydrate, 33% fat) on glucose and insulin responses in women with PCOS and reported greater reductions in fasting insulin (-3 mIU/L) and lower acute insulin response to glucose (-98 mIU/L × 10 minutes) with the moderately low-carbohydrate diet compared to other two diets. In contrast, results from two clinical trials reported no significant differences in glucose or energy metabolism with moderately low-carbohydrate diets.…”
Section: Dietary Carbohydrates and Pcosmentioning
confidence: 99%
See 3 more Smart Citations
“…85 One trial included a diet with <30% carbohydrates, six trials included diets with 40% carbohydrates and four studies with 41-45% carbohydrates. 41,42,76,83,[86][87][88][89][90][91][92] Douglas et al 92 compared the effects of three eucaloric diets: 1) standard (16% protein, 56% carbohydrate, 31% fat), 2) moderately low-carbohydrate (15% protein, 43% carbohydrate, 45% fat) and 3) high monounsaturated fatty acid (MUFA) diets (15% protein, 55% carbohydrate, 33% fat) on glucose and insulin responses in women with PCOS and reported greater reductions in fasting insulin (-3 mIU/L) and lower acute insulin response to glucose (-98 mIU/L × 10 minutes) with the moderately low-carbohydrate diet compared to other two diets. In contrast, results from two clinical trials reported no significant differences in glucose or energy metabolism with moderately low-carbohydrate diets.…”
Section: Dietary Carbohydrates and Pcosmentioning
confidence: 99%
“…76,78,[90][91][92]105,106,152 Moderately low-carbohydrate, high-fat diets have been shown to decrease fasting insulin and AUC for insulin and to increase insulin sensitivity in three trials in women with PCOS. [90][91][92] In one trial, a high-fat, moderately low-carbohydrate eucaloric diet resulted in greater reductions in body fat, intra-abdominal adipose tissue, subcutaneous abdominal adipose tissue and intermuscular adipose tissue compared to a control diet.…”
Section: Dietary Fat and Pcosmentioning
confidence: 99%
See 2 more Smart Citations
“…Two dietary weight loss studies that substituted protein for CHO showed no difference according to macronutrients [30,31], but the effect of weight loss or substitution of protein for CHO may have overridden any benefit from CHO restriction per se in lowering insulin concentrations. Two eucaloric studies with crossover design comparing moderate variations in dietary CHO (55% vs 40%), with mono/polyunsaturated fat substitution, showed significant reduction in fasting insulin after 3-8 weeks [32,33]. Day-long insulin response to replacement of dietary CHO with fat in the eucaloric state has not yet been reported in women with PCOS.…”
Section: Introductionmentioning
confidence: 96%